2014
DOI: 10.1016/j.yjmcc.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy associated Lys104Glu mutation in the myosin regulatory light chain causes diastolic disturbance in mice

Abstract: We have examined, for the first time, the effects of the familial hypertrophic cardiomyopathy (HCM)- associated Lys104Glu mutation in the myosin regulatory light chain (RLC). Transgenic mice expressing the Lys104Glu substitution (Tg-MUT) were generated and the results compared to Tg-WT (wild-type human ventricular RLC) mice. Echocardiography with pulse wave Doppler in 6 month-old Tg-MUT showed early signs of diastolic disturbance with significantly reduced E/A transmitral velocities ratio. Invasive hemodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 43 publications
5
56
1
Order By: Relevance
“…The expression of Mylk3 (gene ID 213435) encoding the mouse cMLCK was assessed in three to four hearts per group by quantitative (qPCR) as described in ref. 27, and at the level of protein using a cMLCK-specific antibody (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of Mylk3 (gene ID 213435) encoding the mouse cMLCK was assessed in three to four hearts per group by quantitative (qPCR) as described in ref. 27, and at the level of protein using a cMLCK-specific antibody (16).…”
Section: Methodsmentioning
confidence: 99%
“…The paraffin-embedded longitudinal sections of the hearts stained with H&E (hematoxylin and eosin) and Masson's trichrome were examined for overall morphology and fibrosis (27). For transmission EM imaging, the hearts were fixed with 2% (vol/vol) glutaraldehyde, and the left ventricles were sectioned longitudinally for imaging as described earlier (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4, 5 Although it has been postulated that myocardial scar may be subsequent to cardiomyocyte death caused by myocardial ischemia and metabolic abnormalities, 1,6 other data have indicated that myocardial scarring could be a primary expression of HCM. 7 The development of genetic testing has enabled the identification of subgroups of HCM based on clinical and genetic information. 8 Recent data revealed that 40% of reviewed all the sequences after a 3-month interval to assess the intraobserver variability.…”
Section: Study Population and Clinical Evaluationmentioning
confidence: 99%
“…Other studies from Szczesna et al's laboratory have also revealed compromised RLC phosphorylation in several different HCM models (Tg-R58Q and Tg-D166V), occurring concurrently with diminished maximal tension and altered Ca 2+ sensitivity of contraction (Abraham et al 2009;Kerrick et al 2009a;Muthu et al 2012b). Studies with HCM causing mutations in the myosin RLC suggest a correlation between the severity of cardiomyopathy phenotype and the level of RLC phosphorylation in vivo (Huang et al 2014;Kerrick et al 2009b;Muthu et al 2012b). The compromised phosphorylation of RLC mutants compared to WT suggests that diminished RLC phosphorylation observed in HCM hearts may have an important physiological role and is central to the understanding of the mutation-elicited detrimental cardiomyopathy phenotype.…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 95%